2013
DOI: 10.1080/21615667.2013.10878970
|View full text |Cite
|
Sign up to set email alerts
|

Age, Psycho-Emotional States and Stress Resistance in Elite Wrestlers

Abstract: In the last decade Olympic sports are characterized by the presence of older athletes who have reached high athletic results. The purpose of the study was to research the age peculiarities of stress resistance and psycho-emotional states in elite wrestlers. A total of 19 elite athletes (a span of ages), all members of the Ukrainian National Team in Greco-Roman wrestling were examined. The perception and processing of visual information, the balance of the nervous system and psycho-emotional stability were stud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
1
0
5

Year Published

2016
2016
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 4 publications
(4 reference statements)
0
1
0
5
Order By: Relevance
“…It was found that achieving a certain level of stress resistance is achieved due to the tension of vegetative regulation [22].…”
Section: Discussionmentioning
confidence: 99%
“…It was found that achieving a certain level of stress resistance is achieved due to the tension of vegetative regulation [22].…”
Section: Discussionmentioning
confidence: 99%
“…Пода-льша обробка отриманих результатів і представ-лення їх у протоколі здійснювалась за допомогою статистичної комп'ютерної програми «Kubios HRV» [8,9].…”
Section: Vikinei13@gmailcomunclassified
“…Найнижчий рівень активації над-низькочастотного спектра RR-інтервалів спостерігається у молодшій віковій групі, найвищий -у спортсменів старшої групи. Ця обставина свідчить про посилення активації нейрогуморальних центрів автономної нерво-вої системи у спортсменів в умовах вікової інволюції [25]. Однак збільшені порівняно із молодшою групою спортсменів значення наднизькочастотного спектра RR-інтервалів у юніорів вказують на недосконалість механіз-му нейрогуморальної регуляції (див.…”
Section: результати та їх обговоренняunclassified